Catherine Clément, dix mille guitares & un bada, rendez-vous avec l’histoire... - Ribeiro Gonçalves, Artur Henrique (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2014)
The sebastianism is the most universal of Portuguese myths. More than four centuries after the battle of Ksar-el-Kebir, some people still believe the return of the Hidden king to save the country and conquer the Fifth Empire. — Catherine Clément offers us a very special interpretation of the facts in the novel Ten thousand guitars (2010). She chose an Indian rhinoceros to tell the story of his European owners: Sebastian of Portugal, Rudolph II of Germany and Christina of Sweden. —The biographical representation of the three crowned heads that unify the narrative has the power to reveal to the reader facets of life that can take charge of black legends derail. Message of hope in our global village, a long way to go in our journey through life...